Estimates of Eddy Heat Flux Crossing the Antarctic Circumpolar Current from Observations in Drake Passage - Watts, D. Randolph; Tracey, Karen L.; Donohue, Kathleen A.; Chereskin, Teresa K. (Journal of Physical Oceanography, 2016)
The 4-yr measurements by current- and pressure-recording inverted echo sounders in Drake Passage produced statistically stable eddy heat flux estimates. Horizontal currents in the Antarctic Circumpolar Current (ACC) turn with depth when a depth-independent geostrophic current crosses the upper baroclinic zone. The dynamically important divergent component of eddy heat flux is calculated. Whereas full eddy heat fluxes differ greatly in magnitude and direction at neighboring locations within the local dynamics array (LDA), the divergent eddy heat fluxes are poleward almost everywhere. Case studies illustrate baroclinic instability events that cause meanders to grow rapidly. In the southern passage, where eddy variability is weak, heat fluxes are weak and not statistically significant. Vertical profiles of heat flux are surface intensified with ~50% above 1000 m and uniformly distributed with depth below. Summing poleward transient eddy heat transport across the LDA of −0.010 ± 0.005 PW with the stationary meander contribution of −0.004 ± 0.001 PW yields −0.013 ± 0.005 PW. A comparison metric, −0.4 PW, represents the total oceanic heat loss to the atmosphere south of 60°S. Summed along the circumpolar ACC path, if the LDA heat flux occurred at six “hot spots” spanning similar or longer path segments, this could account for 20%–70% of the metric, that is, up to −0.28 PW. The balance of ocean poleward heat transport along the remaining ACC path should come from weak eddy heat fluxes plus mean cross-front temperature transports. Alternatively, the metric −0.4 PW, having large uncertainty, may be high.